MODEL PERSAMAAN SIMULTAN PADA ANALISIS HUBUNGAN KEMISIKINAN DAN PDRB PADA PROVINSI JAWA TENGAH TAHUN 2022 - Nanda Putri Qumayroh; Nicolaus Fiermon Hardo, Akmal Yazid Lubis, Terevina Lorensia, Maria Imakulata Kwuta, Kurnia, Vennus (CV. Adiba Aisha Amira, 2024)
This study aims to analyze the factors that affect the poverty rate and economic growth in Central Java Province with a simultaneous equation model approach. Panel data from 35 districts/cities in Central Java in 2022 were used as research samples. The Two Stage Least Square (TSLS) method was chosen for parametric estimation to overcome endogeneity problems in the model. The estimation results show that access to clean water has a negative and significant effect on the poverty rate. Increasing access to clean water by 1 percent contributed to reducing the region's poverty rate by 0.432 percent. This finding is in line with the theory that meeting basic needs such as clean water can improve welfare and reduce poverty in the poor. Meanwhile, the high population growth rate has proven to have a negative impact on slowing economic growth in Central Java. Population growth that increased by 1 percent was related to a decrease in the real GDP growth rate of 0.949 percent. This indicates that an increase in the number of labor forces beyond available employment will result in decreased labor productivity. In conclusion, the simultaneous equation model is able to show empirical evidence of the interplay between poverty problems and regional economic growth. Poverty alleviation efforts through increasing access to basic necessities have a positive impact on accelerating regional growth.